Análisis y retos técnicos del desarrollo de Shale Gas en México - Endo Hernández, Eduardo Khoji (My University, 2015)
Análisis y retos técnicos del desarrollo de Shale Gas en México
Análisis y retos técnicos del desarrollo de Shale Gas en México
Keywords: Análisis y retos técnicos del desarrollo de Shale Gas en México